A first-time investigation of psychosocial inclusivity in design: inclusive supermarket design for older individuals. (11th March 2020) - Lim, Yonghun; Giacomin, Joseph; Yin, Yuanyuan; Nickpour, Farnaz
As a first-time investigation of 'psychosocial inclusivity' in design, this paper introduces and establishes the concept of psychosocially inclusive design, and explores it within the context of supermarket shopping for older individuals, as one instrumental activity of daily living. Inclusive design theory and practice have been predominantly concerned with issues of physical access, limiting its scope and relevance to the wider more complex psychosocial issues. Employing research triangulation and rigorous empirical investigations, this paper advances the fundamental understanding, extends the general research agenda, and pushes the current boundaries of inclusive design towards non-physical inclusion by identifying any possible psychosocial constructs. Four constructs including 'cognitive', 'emotional', 'social', and 'value' were identified in the context of supermarket shopping through ethnographic interviews; creative workshop; and observations conducted with a total of 58 older individuals. The results may play a crucial role in establishing the theoretical foundations to the concept of psychosocial inclusivity in design.